Retraction: a highly concise and practical route to clavaminols, sphinganine and (+)-spisulosine via indium mediated allylation of α-hydrazino aldehyde and a theoretical insight into the stereochemical aspects of the reaction - Pandey, M.; Chowdhury, P. S.; Dutta, A. K.; Kumar, P.; Pal, S. (RSC Advances, 2019)
A conceptually different approach has been employed for the synthesis of 1,2-amino alcohols by proline-catalyzed α-amination of aldehyde and one-pot indium mediated allylation of the crude α-hydrazino aldehydes. DFT based quantum chemical calculations have been performed to obtain a quantitative explanation of the stereoselectivity of the reaction.